Financial Performance of Islamic and Conventional Banks in Malaysia: A Comparative Analysis - Ahmed Sulub, Yasin; Che Mohd Salleh, Marhanum (New Millennium Discoveries, 2019)
This paper analyses the financial performance of Islamic (IB) and conventional banks (CB) in Malaysia comparatively, within the scope of a dual setting arrangement in the Malaysian financial industry. Performance evaluation of both types of banks relies on ratio analyses which include Return on Equity (ROE), Return on Assets (ROA), Earnings per Share (EPS) and Debt Ratio. Data for this study covers four full-fledged IBs and four CBs in the period between 2012 and 2016. Based on statistical analysis (ttest and correlation analysis), the average of ROE was 6% for IBs and 14% for CBs. Results of t-test reveals that this higher performance of CBs is significant (ttest=1.957, p-value= 0.029). Furthermore, both ROA and EPS were significantly different between the two groups at p-value less than 1%. These results indicate that the Malaysian CBs performed better than IBs, at least for the banks included in this study. In terms of debt ratio, (the percentage of liabilities to total assets), IBs carry more debts than CBs. The risk of this higher debt is that the bank may be at risk of bankruptcy and may not be able to pay its obligations on time. The difference between the average debt of the two groups is significant at less than 5% (t-test= -2.251, pvalue= 0.015). Therefore, not only is IBs’ performance inferior to CBs but their debt ratio is also higher. This research has implications for IBs; they should further improve their performance to become more competitive in the current environment for the financial industry. More importantly, IBs need to uphold Islamic ethics throughout their business operations to ensure that both the stated principles and subsequent objectives are achieved.